A sociological study of the Five Hundred Houses Project in Mihindusenpura - Fernando, A. (University of Colombo, 2017)
Urban development is emerging as a key priority in Sri Lanka. However, the social costs of development are often ignored in the construction of highways, flyovers, condominiums, and other large scale development projects. Human beings, families, and communities are embroiled in the process of development. The overall objective of this study is to ascertain the impact of development-induced displacement in Mihindusenpura, Dematagoda, in the Colombo Municipal Council area. The specific research objectives are to explore the quality of life of the community pre- and postresettlement; the expectations and fears of the urban community; and the social impact of resettlement in condominiums. The cross sectional study design focussed on the experiences of the sample population during 2013-2017. The study population was the Mihindusenpura 500 Houses project, of which 100 households were selected (50 houses from each condominium). The initial sampling method was simple random sampling; this had to be altered when selected household respondents could not be contacted at home. Data was collected from September 2015 to March 2017. The methods were a household survey administered through a semi-structured questionnaire; twenty case studies conducted with selected respondents; recording of observations and interactions with the community; and interviews with community leaders. The findings of the study identified factors that play a role in the lives of the community such as dangers of unplanned development; change in social status and upward social mobility; breakdown in community networks and social isolation; and the impact on social institutions and the resulting insecurity within the community. The study concludes that while urban development projects are designed to be beneficial to people, the lack of a people-centred focus in urban development, the prevalence of aggressive planning tactics, and the lack of strong housing policies create greater vulnerability and result in the impoverishment of the targeted communities.
Keywords: urban development, people-centred